BETWEEN MARGINALIZATION AND ACCEPTANCE - MENTALLY DISABLED PERSONS IN SOCIAL CONTEXT - SOPONARU, Camelia; DIRTU, Catalin; IOAN, Beatrice-Gabriela; IORGA, Magdalena (Studia Universitatis Babeş-Bolyai Bioethica, 2016)
The aim of the study is to identify opinions related to mentally disabled people among students. Material and method: 85 students were included in the research; only 26% declared that they had experience with mentally disabled (MD) people. The instrument used was an open-answer questionnaire, which investigation of the following dimensions: the concept of mental disability (the cognitive vs. global perspective), the image of mentally disabled people (characteristics, capacities, disabilities), social integration (social perception, support measures, support institutions, vocational options), education (types of schooling, adjustment problems, relational, behavioral, educational problems and perspectives after graduation). The transcription of interviews was followed by a qualitative analysis performed with the freeware version of the QDA Miner 4 Lite software. Results: The most frequent issues revealed by our study have been the behavioral ones (82%) and 92% of subjects associates MD with loosing social integration and autonomy. 58% of the participants correlate MD with the cognitive impairment; 52% sustain that public institutions must take care of mentally disabled persons. Conclusions: The subjects tend to assess the mentally disabled personality globally, focusing on the diversity of aspects of the mentally disabled personality, and less schematically, focusing only on cognitive aspects specific to mental disability, emphasizing the various non-functional cognitive aspects of the mentally disabled individuals. Între marginalizarea și acceptarea persoanelor cu handicap mental în context social. Scopul studiului este de a identifica opiniile studenților cu privire la persoanele cu deficienţă mentală. Material şi metode: 85 de studenţi au fost incluşi în cercetare. Dintre aceștia, doar 26% au declarat că au avut experienţe anterioare cu persoane cu deficienţă mentală. Instrumentul folosit a fost un chestionar cu răspunsuri deschise care a investigat următoarele dimensiuni: conceptul de deficiență mintală (perspectiva cognitivă vs perspectiva globală), imaginea persoanelor cu deficiență mintală (caracteristici, capacități, dizabilități), integrare în societate (percepția socială, măsuri de sprijin, instituții de sprijin, opțiuni vocaționale), educație (tipuri de școlarizare, probleme de adaptare, relaționale, comportamentale, educative și perspective post-absolvire). Transcrierea interviurilor a fost urmată de analiză calitativă efectuată cu ajutorul programului QDA Miner 4 Lite. Rezultate: cele mai multe dintre problemele asociate sunt legate de comportament (82%) şi 92% dintre subiecţi asociază deficienţa mentală (DM) cu incapacitatea de integrare socială şi autonomie. Un total de 58% corelează DM cu degradarea cognitivă; 52% dintre participanți susţin că instituţiile publice ar trebui să aibă grijă de persoanele cu DM. Concluzii: Participanții tind să evalueze personalitatea deficientului mintal mai mult global, cu o centrare pe diversitatea aspectelor personalității sale, și mai puțin schematic, centrat doar pe aspectele cognitive specifice deficienței mintale, accentuând diversele aspecte cognitive nefuncționale în cazul deficienței mintale. Cuvinte-cheie: dizabilitate mentală, discriminare, vulnerabilitate, studenţi.